Pembrolizumab monotherapy for previously treated metastatic triple-negative breast cancer: cohort A of the phase II KEYNOTE-086 study - Adams, S; Schmid, P; Rugo, H S; Winer, E P; Loirat, D; Awada, A; Cescon, D W; Iwata, H; Campone, M; Nanda, R; Hui, R; Curigliano, G; et al. (Annals of oncology, 2019)
Treatment options for previously treated metastatic triple-negative breast cancer (mTNBC) are limited. In cohort A of the phase II KEYNOTE-086 study, we evaluated pembrolizumab as second or later line of treatment for patients with mTNBC. Eligible patients had centrally confirmed mTNBC, ≥1 systemic therapy for metastatic disease, prior treatment with anthracycline and taxane in any disease setting, and progression on or after the most recent therapy. Patients received pembrolizumab 200 mg intravenously every 3 weeks for up to 2 years. Primary end points were objective response rate in the total and PD-L1-positive populations, and safety. Secondary end points included duration of response, disease control rate (percentage of patients with complete or partial response or stable disease for ≥24 weeks), progression-free survival, and overall survival. All enrolled patients (N = 170) were women, 61.8% had PD-L1-positive tumors, and 43.5% had received ≥3 previous lines of therapy for metastatic disease. ORR (95% CI) was 5.3% (2.7-9.9) in the total and 5.7% (2.4-12.2) in the PD-L1-positive populations. Disease control rate (95% CI) was 7.6% (4.4-12.7) and 9.5% (5.1-16.8), respectively. Median duration of response was not reached in the total (range, 1.2+-21.5+) and in the PD-L1-positive (range, 6.3-21.5+) populations. Median PFS was 2.0 months (95% CI, 1.9-2.0), and the 6-month rate was 14.9%. Median OS was 9.0 months (95% CI, 7.6-11.2), and the 6-month rate was 69.1%. Treatment-related adverse events occurred in 103 (60.6%) patients, including 22 (12.9%) with grade 3 or 4 AEs. There were no deaths due to AEs. Pembrolizumab monotherapy demonstrated durable antitumor activity in a subset of patients with previously treated mTNBC and had a manageable safety profile. ClinicalTrials.gov, NCT02447003.